2015
DOI: 10.1007/s00018-015-2000-5
|View full text |Cite
|
Sign up to set email alerts
|

Tubulin acetylation: responsible enzymes, biological functions and human diseases

Abstract: Microtubules have important functions ranging from maintenance of cell morphology to subcellular transport, cellular signaling, cell migration, and formation of cell polarity. At the organismal level, microtubules are crucial for various biological processes, such as viral entry, inflammation, immunity, learning and memory in mammals. Microtubules are subject to various covalent modifications. One such modification is tubulin acetylation, which is associated with stable microtubules and conserved from protists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
184
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(204 citation statements)
references
References 203 publications
(444 reference statements)
3
184
0
1
Order By: Relevance
“…CK2 was shown to increase HDAC6 activity either by direct HDAC6 phosphorylation (46) or by priming GSK3β, which interacts with HDAC6 and enhances its activity by increasing HDAC6 phosphorylation at Ser22 (45). Acetylation of α-tubulin contributes to microtubule stability, and α-tubulin deacetylation via increased HDAC activity was suggested to lead to microtubule instability and cell motility (44,45). Along this line, a recent work in a mouse model of familial dysautonomia showed that reduced levels of IκB kinase complex-associated protein (IKAP) lead to increased HDAC6 levels in sensory neurons, thereby reducing acetylated α-tubulin and provoking microtubule instability (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CK2 was shown to increase HDAC6 activity either by direct HDAC6 phosphorylation (46) or by priming GSK3β, which interacts with HDAC6 and enhances its activity by increasing HDAC6 phosphorylation at Ser22 (45). Acetylation of α-tubulin contributes to microtubule stability, and α-tubulin deacetylation via increased HDAC activity was suggested to lead to microtubule instability and cell motility (44,45). Along this line, a recent work in a mouse model of familial dysautonomia showed that reduced levels of IκB kinase complex-associated protein (IKAP) lead to increased HDAC6 levels in sensory neurons, thereby reducing acetylated α-tubulin and provoking microtubule instability (56).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the homeostatic changes in AIS induced by sustained M-current inhibition were independent of L-type Ca 2+ channel activity but were contingent on the crucial AIS component, protein kinase CK2. Recent studies suggest that CK2 leads to microtubule destabilization and stimulates microtubule dynamics by increasing the activity of the tubulin deacetylase HDAC6 (44)(45)(46). Thus, we checked the impact of 100 nM taxol, a microtubule stabilizer, on the distal redistribution of FGF14 induced by 4 h of XE991 exposure.…”
Section: Inhibition Of Ck2 Prevents the Adaptive Changes In Intrinsicmentioning
confidence: 99%
“…3,4 Changes in tubulin post-translational modifications have been associated with neurodegenerative disorders, cancer, heart diseases and other pathological conditions. 5,6 Stable microtubules are well known to contain acetylated tubulin, which is one of the major post-translational modifications of microtubules. Acetylation tubulin has been implicated in the differentiation of microtubule structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, tubulin PTMs are potential regulators of this process as much as, for long time, acetylated MTs were referred almost synonymously to old and stable MTs. Indeed, among its several biological functions [14], it has been shown that acetylation accumulates during MT aging and it has been proposed that the MT-acetylase α Tubulin Acetyl Transferase1 (αTAT1) can act as a clock for MT lifetimes [15], due to its preference for MTs and its low catalytic rate. Nevertheless, other candidates may be responsible for minor tubulin acetylation in vivo, including Elongator Complex Protein Elp3, which acts as tubulin acetylase, controlling the development and the migration of cortical neurons [16].…”
mentioning
confidence: 99%
“…A reliable alternative can be the fine modulation of MT acetylation, which seems to be tightly associated to axonal transport and locomotor defects [16,36,38]. Since the extent of MT acetylation depends on the balance of the antagonistic acetylases and deacetylases activities, its modulation can be achieved by the use of specific stimulators or inhibitors of αTAT1 or Histone Deacetylase 6 (HDAC6) [14]. The latter specifically acts on tubulin [40], and its inhibition exerts neuroprotection in many age-related neurodegenerative disorders [41] and rescues the transport defects observed in Huntington's disease [37].…”
mentioning
confidence: 99%